1972
DOI: 10.1111/j.1528-1157.1972.tb04403.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral pO2, pCO2 and pH: Changes During Convulsive Activity and their Significance for Spontaneous Arrest of Seizures

Abstract: SUMMARY The present study on rats and cats aimed to clarify the role played by hypoxia, hypercapnia and acidosis in spontaneous arrest of seizures. In most experiments cortical pO2 declined during seizure activity, whereas pCO2 increased. Occasionally, however, reverse reactions occurred. Since the increase in cortical blood flow varied over a wide range, it could account for the fact that gas tension did not always change in the same direction or to the same degree during a seizure. Cessation of seizure act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
63
0
1

Year Published

1976
1976
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(73 citation statements)
references
References 52 publications
(44 reference statements)
7
63
0
1
Order By: Relevance
“…Apparently, the coupling between cerebral oxidative metabolism and blood flow is such that a recovery period is required for a full return to responsiveness following each burst of parox ysmal activity. This idea is supported by reports describing progressive decreases in cerebrovas cular reactivity (Kontos et aI., 1978;Blennow et aI., 1979), cerebrovascular resistance (Magnaes and Nomes, 1974), and the magnitude of phasic increases in CBF (Shalit, 1965;Caspers and Speckman, 1972) during recurrent seizures. These cerebrovascular changes already have been impli cated in the transition of cerebral P02 responses from increases to decreases and cytochrome a,a3 responses from oxidations to reductions (Caspers and Speckman, 1972;Kreisman et al, 1981bKreisman et al, , 1983a.…”
Section: Influence Of Timing Of Repeated Ictal Bursts On Vascular Andmentioning
confidence: 62%
See 1 more Smart Citation
“…Apparently, the coupling between cerebral oxidative metabolism and blood flow is such that a recovery period is required for a full return to responsiveness following each burst of parox ysmal activity. This idea is supported by reports describing progressive decreases in cerebrovas cular reactivity (Kontos et aI., 1978;Blennow et aI., 1979), cerebrovascular resistance (Magnaes and Nomes, 1974), and the magnitude of phasic increases in CBF (Shalit, 1965;Caspers and Speckman, 1972) during recurrent seizures. These cerebrovascular changes already have been impli cated in the transition of cerebral P02 responses from increases to decreases and cytochrome a,a3 responses from oxidations to reductions (Caspers and Speckman, 1972;Kreisman et al, 1981bKreisman et al, , 1983a.…”
Section: Influence Of Timing Of Repeated Ictal Bursts On Vascular Andmentioning
confidence: 62%
“…This idea is supported by reports describing progressive decreases in cerebrovas cular reactivity (Kontos et aI., 1978;Blennow et aI., 1979), cerebrovascular resistance (Magnaes and Nomes, 1974), and the magnitude of phasic increases in CBF (Shalit, 1965;Caspers and Speckman, 1972) during recurrent seizures. These cerebrovascular changes already have been impli cated in the transition of cerebral P02 responses from increases to decreases and cytochrome a,a3 responses from oxidations to reductions (Caspers and Speckman, 1972;Kreisman et al, 1981bKreisman et al, , 1983a. Collectively, these data suggest that transition from oxygen sufficiency to insufficiency during recurrent seizures is caused by uncoupling of appropriate ce rebrovascular responses from neuronal and meta bolic activity.…”
Section: Influence Of Timing Of Repeated Ictal Bursts On Vascular Andmentioning
confidence: 62%
“…The exact mechanisms by which tissue pH and neuronal density may influence each other are not known yet. Changes in the physiological parameters of neurons and glial cells, and alterations in glutamate uptake and calcium metabolism, have been associated with changes in the intracellular or extracellular tissue pH (Balestrino and Somjen, 1988;Caspers and Speckmann, 1972;Dipolo and Beauge, 1982;Goldman et al, 1989;Gruol et al, 1980;Pappas et al, 1994;Robello et al, 1994;Takahashi et al, 1995). It is also known that changes in tissue pH are associated with certain pathological conditions such as ischemia or head injury (Billups and Attwell, 1996;Cadoux-Hudson et al, 1990;Smith et al, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…Ingvar et al (1962) and Meyer et al (1966) reported that seizure activity of the cerebral cortex was accom panied by a decrease in local tissue Po 2 • From their measurements of the diameter of pial arteries before and after administration of metrazol, Wei et al (1977) deduced that during seizures dilation was mediated, at least in part, by activation of a meta bolic mechanism dependent on the production of tissue hypoxia. Caspers and Speckmann (1972) found a reduction of tissue P0 2 predominating during the seizure attacks. However, the rate of repetition of convulsions was important regarding the role of tissue Po 2 • During the first convulsions in a series, tissue P0 2 tended to rise rather than to fall.…”
mentioning
confidence: 98%